Biomechanical investigation of lumbar hybrid stabilization in two-level posterior instrumentation - Hegewald, Aldemar Andres (European spine journal, 2017)
PurposeHybrid stabilization with a dynamic implant has been suggested to avoid adjacent segment disease by creating a smoother transition zone from the instrumented segments to the untreated levels above. This study aims to characterize the transition zones of two-level posterior instrumentation strategies for elucidating biomechanical differences between rigid fixation and the hybrid stabilization approach with a pedicle screw-based dynamic implant.MethodsEight human lumbar spines (L1-5) were loaded in a spine tester with pure moments of 7.5 Nm and with a hybrid loading protocol. The range of motion (ROM) of all segments for both loading protocols was evaluated and normalized to the native ROM.ResultsFor pure moment loading, ROM of the segments cranial to both instrumentations were not affected by the type of instrumentation (p > 0.5). The dynamic instrumentation in L3-4 reduced the ROM compared to intact (p < 0.05) but allowed more motion than the rigid fixation of the same segment (p < 0.05). Under hybrid loading testing, the cranial segments (L1-2, L2-3) had a significant higher ROM for both instrumentations compared to the intact (p < 0.05). Comparing the two instrumentations with each other, the rigid fixation resulted in a higher increased ROM of L1-2 and L2-3 than hybrid stabilization.ConclusionsRegardless of the implant, two-level posterior instrumentation was accompanied by a considerable amount of compensatory movement in the cranial untreated segments under the hybrid protocol. Hybrid stabilization, however, showed a significant reduction of this compensatory movement in comparison to rigid fixation. These results could support the surgical strategy of hybrid stabilization, whereas the concept of topping-off, including a healthy segment, is discouraged.
Gesehen am 02.10.2018